2018
DOI: 10.1039/c8nr01383g
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes (CNTs) based advanced dermal therapeutics: current trends and future potential

Abstract: The search for effective and non-invasive delivery modules to transport therapeutic molecules across skin has led to the discovery of a number of nanocarriers (viz.: liposomes, ethosomes, dendrimers, etc.) in the last few decades. However, available literature suggests that these delivery modules face several issues including poor stability, low encapsulation efficiency, and scale-up hurdles. Recently, carbon nanotubes (CNTs) emerged as a versatile tool to deliver therapeutics across skin. Superior stability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…Aside from occupational exposures, new biomedical technologies are being developed that could increase skin exposure to CNTs. Specifically, CNTs are being developed as transdermal drug delivery devices [1315], bio-sensing patches [16–19], and “smart” textiles [2022]. While these technologies are in the early stages of development, additional dermal toxicological studies of CNTs are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from occupational exposures, new biomedical technologies are being developed that could increase skin exposure to CNTs. Specifically, CNTs are being developed as transdermal drug delivery devices [1315], bio-sensing patches [16–19], and “smart” textiles [2022]. While these technologies are in the early stages of development, additional dermal toxicological studies of CNTs are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…As Kuche et al explained in their review work, the major drawbacks of existing transdermal delivery patches are the low drug release rate and the poor skin permeability [100]. CNT based nanocomposites could bring an innovative solution to both problems thanks to their intrinsic properties.…”
Section: Cnt-based Hydrogels For Biomedical Applicationsmentioning
confidence: 99%
“… A brief historical timeline for CNTs showing the major developments that guided applications of CNTs [ 19 ]. …”
Section: Figurementioning
confidence: 99%
“…It has been confirmed that CNTs exhibit ultra-high-modulus and strength, and also have anisotropic electrical conductivity when incorporated in a matrix, they can remarkably enhance fabricated nanocomposites. The CNTs are used in many other applications like sensors, transistors, field emission sources, voltage inverters, [ 16 , 17 ], solar cells, fuel cells, energy storage devices [ 18 ], drug-delivery systems and biosensors [ 19 ]. Therefore, new opportunities and research directions for developing novel metal matrix nanocomposites (MMNCs) could be opened up by applying nanotechnology in material science and engineering.…”
Section: Introductionmentioning
confidence: 99%